PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI PENERAPAN PEMBELAJARAN MODEL PROBLEM BASED LEARNING (PBL) SISWA PADA MATA PELAJARAN IPS/ EKONOMI KOMPETENSI DASAR MANUSIA SEBAGAI MAKHLUK SOSIAL DAN EKONOMI KELAS VII.A SEMESTER GANJIL DI SMP NEGERI - Ika Hidayati; Miftahus Surur (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
Problem-based learning (Problem Based Learning), is one of the innovative learning model that can provide an active learning conditions for students. PBL is a learning model that engages students to solve a problem through the stages of scientific methods so that students can learn knowledge related to these issues and also have the skills to solve problems (Ward, 2002). The object of research is VII.B graders were 26 people. The design of this study is modeled by using the scheme Hopkins Tagart 4 phases: planning, action / action, observation and reflection. To obtain the data in this study using observation, interview and test. Data analysis in this study used a qualitative descriptive analysis. The results of preliminary or repeat the test before the action can be seen that 35.71 This increase also occurred in student activities while following lesson pembelajara using Problem Based Learning (PBL), the observations of student learning activities before the measures amounted to 83.33 percent of the student activity % the activity of a sufficient criterion. While the results of observations made on the implementation of the first cycle of learning keativan students reach 87,18% by the activity of both criteria, and having carried on observations of student learning activities seem very good increased activity of the percentage of students reaching 88.78%. At this stage of reflection carried out by researchers and observers are analyzing the results obtained from the observation of student activity, from the observation of student activity on the implementation of the second cycle it seems there is an increase compared to the average score achieved in the implementation of the first cycle of 85 , 25% to 88.78%. From all the research that has been carried out then the researchers can take the conclusion that the application of learning to Problem Based Learning (PBL) can enhance the activity and student learning outcomes in social studies / Economics Competence Basic Human Beings For Social and Economic odd semester class VII.B at SMP Negeri 2 Kendit Academic.